The New idea in education - Jonasson, Jonas (New York : Hyperion, 2012)
After a long and eventful life, Allan Karlsson ends up in a nursing home, believing it to be his last stop. The only problem is that he's still in good health, and in one day, he turns 100. A big celebration is in the works, but Allan really isn't interested (and he'd like a bit more control over his vodka consumption). So he decides to escape. He climbs out the window in his slippers and embarks on a hilarious and entirely unexpected journey, involving, among other surprises, a suitcase stuffed with cash, some unpleasant criminals, a friendly hot-dog stand operator, and an elephant (not to mention a death by elephant). It would be the adventure of a lifetime for anyone else, but Allan has a larger-than-life backstory: Not only has he witnessed some of the most important events of the twentieth century, but he has actually played a key role in them. Starting out in munitions as a boy, he somehow finds himself involved in many of the key explosions of the twentieth century and travels the world, sharing meals and more with everyone from Stalin, Churchill, and Truman to Mao, Franco, and de Gaulle.
Keywords: ACTION AND ADVENTURE -- FICTION